Memorization in Early Literacy: A Reflective Study of Spelling Bee Practices in Primary Education - Sitti Maryam (Ma'soem University, 2026)
This reflective case study explores how a spelling bee competition can transform the researcher’s perception of memorization from a mechanical task into an engaging, meaningful experience. Conducted at private school running international curriculum in Makassar, the event involved preparatory and lower primary students aged five to eight, competing through written and oral rounds. Data were collected through classroom observation, teacher notes, and post-event reflections. The findings address the research objectives thematically. They reveal that memorization, when embedded in a playful and competitive format, supports not only cognitive development but also social interaction and emotional growth. The event fostered students’ confidence, cooperation, and enthusiasm for learning English. Reflecting as both teacher and lecturer, the researcher argues that small-scale events like this merit scholarly attention, as they reveal the pedagogical value of joy, curiosity, and community participation in early language learning.